On the Course "Time-Cost Project Optimization" and My Adventure with E-Learning - Gaspars-Wieloch, Helena (Studia Oeconomica Posnaniensia, 2015)
More and more lecturers and students recognise the advantages of e-learning, although some academics are still sceptical about the possibilities offered by distance education. In this paper the author shares her experiences relating to the preparation of teaching materials for an e-learning course entitled "Time-cost project optimization", created within the framework of the "Kadry dla Gospodarki" (Human Resources for the Economy) project, and to the functioning of this course. In her opinion, despite some inconveniences that accompany e-education, such a form of education has more benefits than shortcomings as it enables teachers to implement the aim intended by the reformers of the higher education system, which is to stimulate students to be more independent, creative and efficient during studies